A critical review of test methods and alternative scientific approaches to compliance and safety evaluation of paper and board for food contact - Störmer, Angela; Hetzel, Lisa; Franz, Roland (Frontiers in Chemistry, 2024)
Paper and board are widely used as food contact materials. For such sensitive applications, consumer safety regarding transfer of chemical components and contaminants to the food needs to be established. Such safety assessments are becoming increasingly challenging as not only intentionally added substances but also non-intentionally added ones are to be considered. In the European Union, compliance testing and safety evaluation of paper in food contact is largely based on national legislation and standards. The underlying tests are more conventional methods, often overestimating the migration into food, sometimes also underestimating. In this article, the relevant standard test methods are contrasted with currently available scientific knowledge. The scientific approaches to develop and identify suitable test methods are critically reviewed. Furthermore, theoretical predictions via mathematical modelling with the aim to simulate transfer to food realistically are presented and discussed in comparison to available migration studies with foods. Objectives are (i) to summarize the actual scientific knowledge in the field and draw conclusions regarding the potential and limitations of the existing test methods and (ii) identify research gaps towards a better qualitative and quantitative understanding of transport processes of both volatiles and non-volatiles substances from paper and board into foods.